Pengaruh Teknologi Hijau dan Green Intellectual Capital terhadap Kinerja Keberlanjutan pada Perusahaan Pertambangan Batu Bara di Indonesia - Darwis, Ananda Octavia; Saputra, Praja Hadi; Nurfadillah , Mursidah (Balance : Jurnal Akuntansi dan Manajemen, 2025)
The purpose of this study was to analyze the effect of green technology and Green Intellectual Capital on sustainability performance. This research was conducted using quantitative methods. The data used is secondary data. This study uses 34 coal mining companies listed on the Indonesia Stock Exchange which were selected by purposive sampling method in the 2020-2023 period. The analysis technique used in this research is multiple linear regression which is accompanied by other tests such as descriptive statistics and classical assumption tests. The result of this study is that green technology shows a positive direction of influence on sustainability performance, but the test results show that this influence is not significant and statistically declared to have no effect. Similar results are also found in the GIC variable which shows a positive direction of influence on sustainability performance, but the test results show that the influence is not significant and statistically declared to have no effect.